Implementasi Konsep Total Quality Management (TQM) William Edward Deming dalam Pengembangan Mutu Peserta Didik Program Pembelajaran Intensive Science Class (ISC) MAN 1 Darussalam Ciamis Jawa Barat - Rima Majidah (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah, Institut Agama Islam Darussalam (IAID) Ciamis Jawa Barat, 2021)
MAN 1 Darussalam Ciamis is a favorite Madrasah Aliyah Negeri located in Ciamis, West Java. This madrasah has a unique learning program, namely the Intensive Science Class (ISC) learning program, which is the first flagship learning program established in Ciamis, West Java, this is solely implemented to improve the quality of existing students. This study examines problems related to the concept of Total Quality Management (TQM) in intensive science class (ISC) learning programs in improving the quality of its students, which prioritizes customer satisfaction services aka students of Intensive Science Class (ISC) learning programs. Theoretically this research is useful to contribute thinking to the development of concepts and theories that have been widely put forward before. While practically this research can be used as a development of pre-existing research that can then be applied by the head of intensive science class (ISC) learning program in activities related to quality management of Intensive Science Class (ISC) learning program. The research method used in this study is qualitative research with descriptive type, researchers analyze the words of data or redactions produced from various sources of research data. The data sources in this study are the head of the learning program, the class learning teacher, the tutorial learning teacher and the Intensive Science Class (ISC) student learning program. The results of this study show that in the urgency of the Total Quality Management (TQM) approach in developing the quality of students of intensive science class (ISC) learning programs is needed, because one of the concepts of Total Quality Management (TQM) is to implement customer satisfaction services. Then the implementation of the Total Quality Management (TQM) approach in the development of the quality of students of intensive science class (ISC) learning program is through 4 stages, namely planning (plan), implementation (do), learning / examination (study) and action (act). Then the results of the output and outcomes of the Total Quality Management (TQM) approach in the development of quality of students of intensive science class (ISC) learning programs that have produced graduates and achievements of quality and significant, while efforts to produce quality outcomes one of them by using intensive learning methods.